Determinants of agricultural water demand in China. (15th March 2021) - Li, C.; Jiang, T.T.; Luan, X.B.; Yin, Y.L.; Wu, P.T.; Wang, Y.B.; Sun, S.K.
Abstract: The scarcity of water resources significantly restricts the development of human society. Since agriculture is a water-intensive industry, reasonable planning of agricultural water use is quite essential to guarantee food security. Since the determinants of agricultural water demand remain unclear so far, this study has used the Logarithmic Mean Divisia Index (LMDI) decomposition method to analyze the contribution of the four factors (water use efficiency, productivity, planting structure, and production scale) to the agricultural water demand of 5 staple crops in China. From 1997 to 2017, agricultural water demand in China has experienced a decrease before 2003, followed by a steady increase. Productivity, water use efficiency, planting structure, and production scale are the main factors that affect agricultural water demand. Among them, water use efficiency and planting structure adjustment had played a role in promoting the decline of China's agricultural water demand during the study period. The increase in productivity will increase water use efficiency, thereby reducing agricultural water demand. However, the large-scale expansion of production had offset the role of improved productivity and resulted in an increase in agricultural water demand during the study period. The provincial-level results illustrated obvious spatial difference, that acreage contributed the most among four factors. To alleviate agricultural water demand, it would be essential to increase water use efficiency, improve irrigation technology rather than input more water resources to expand production scale. This study provided a key link between the indicators selected for many researches on water resources, and detailed insights for policy-makers on agricultural water sustainability. Highlights: A driving force analysis method of agricultural water demand is proposed. Four driving factors of agricultural water demand are analyzed in China. Increase in water use efficiency and planting structure change contribute to reduce agricultural water demand. Production scale contributed the most among four factors in the provincial decomposition.